Hikers perception towards hiking permit application process at Cameron Highlands - Adnan, Amir Hidayat (2019)
This study was conducted in Cameron Highlands because the Cameron Highlands Forest Department (CHFD) introduced an online permit application system. CHFD is Malaysia's first forest department that using this system. The main purpose of this study is to assess the perception of hikers on this newly introduced system. In addition, this study also wanted to know the problems encountered by hikers during the permit application process as well as suggestions from climbers to improve existing systems. The questionnaire was used to obtain the data and 145 respondents were selected based on the criteria set out in this study. All data were analyzed by Descriptive Analysis. The hiker's perceptions were measured using the Likert Scale. Based on the results of the study, the majority of respondents said that current online system applicable but improvement need to be considered in term of time effective and cost effective.